Single-diode model and two-diode model of PV modules: A comparison - Alrahim Shannan, N.M.A. (2013)
This paper proposes a comparison between single-diode model and two-diode model of photovoltaic (PV) module. The main concern of this work is the accuracy, number of unknown parameters, and the execution time for the unknown parameters, under standard test conditions (STC), in each model. The proposed work tests the accuracy of both models under different temperature conditions using two types of solar modules. The accuracy of each model is tested in terms of maximum power and maximum voltage, and compared to justify the pros and cons of each model. Â© 2013 IEEE.